Toxicity studies of 5-amino-o-cresol administered dermally to F344/NTac rats and B6C3F1/N mice. (Toxic Rep Ser, 2015)
5-Amino-o-cresol is used as an oxidative dye coupler (secondary intermediate) or oxidative (permanent) in hair dye formulations. It was nominated for study by the National Cancer Institute because it is a widely used genotoxic hair dye component for which no cancer studies have been reported. Male and female F344/NTac rats and B6C3F1/N mice were administered 5-amino-o-cresol (greater than 99% pure) dermally for 3 months. Genetic toxicology studies were conducted in Salmonella typhimurium, peripheral blood erythrocytes of male and female mice, and bone marrow of male mice. (Abstract Abridged).